Wavefront aberration in the reconstructed images of holograms on DMDs - Jung Young Son, Beom-Ryeol LEE, Wookho Son, Gwanghee Heo, Tetiana Venkel (TechRxiv, 2022)
Wavefronts of the reconstructed images from holograms displayed on both rhomb and square pixel type DMDs are visually identified with a color phase map obtained with a Shack-Hartmann wavefront sensor to show wavefront aberration induced by DMDs’ unique pixel structure and working principle. The wavefronts of different holograms show very similar color phase maps to each other. But the phase maps reveal clearly the presence of the aberration and indicate that the square pixel DMD which has around two times bigger in dimension compared with the rhomb reveal that its wavefronts are aberrated more than those of the rhomb. In addition to this revelation, they also informs that the aberration is appearing along the DMDs’ pixel rotation directions. This aberration makes the reconstructed images to be blurred and distorted. But when the phase maps are compensated by that of the reflected beam from the On-states of the DMD surfaces without any hologram loading, the reconstructed images becomes more distinguished and identified for both DMDs
Keywords: Reconstructed image holograms rhomb and square pixel DMD Shack-Hartmann wavefront sensor color phase map wavefront aberration